Factors affecting the sale price of bred heifers, bred cows, and beef bulls marketed and sold throughout the United States - Smith, Maggie Jean (Kansas State University, 2020)
Within cow-calf production, the selection of a herd bull and females are important decisions for producers. Across marketing venues, potential buyers of bred females and beef bulls are often provided with various informational at the time of sale. Information often includes physical descriptors, genetic factors, and management and marketing traits. The value of bred females and beef bulls may vary depending on the priorities and goals of the specific buyer. Continued research to better clarify the factors affecting sale price across breeding cattle classes may be of value to the beef cattle industry. Throughout the first chapter, a review of literature surrounding the factors affecting the sale price of bred females and beef bulls is provided. Subsequently, two studies were conducted that investigated potential factors affecting sale price. Within the second chapter, effects of various lot characteristics, physical attributes, and management traits are examined to determine their influence on the sale price of bred heifers sold from 2010 through 2018 and bred cows sold from 2011 through 2018 through video auctions. Findings suggest that multiple elements influence the sale price of bred heifers and bred cows, including auction year or time of sale, breed description, and various physical attributes. The third chapter summarizes research investigating the effect of selection indices and EPDs on the sale price of Red Angus bulls marketed and sold across the United States from 2017 through 2019. Results suggest a relationship between sale price and genetic information but indicate that other factors not captured within the data – such as physical attributes, marketing strategies, and the value of breeder reputation – may be further affecting the sale price of beef bulls. These studies further support the idea that producers consider a combination of marketing factors, physical attributes, genetic traits, and management characteristics when making selection decisions.
Keywords: Bred heifers; Bred cows; Beef bulls; Sale price; Beef cattle